PENGEMBANGAN PLATFORM DECODIFY BERBASIS WEB DENGAN SIMULASI INTERAKTIF KRIPTOGRAFI - Nurul Sahara, Nenden; Yopi Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of digital technology has increased the need for information security, making cryptography a crucial competency for students in information technology and cybersecurity fields. However, cryptography learning in many educational institutions remains predominantly theoretical, causing students to struggle in understanding the actual mechanisms of encryption and decryption algorithms due to the lack of visual representation. Previous studies have attempted to address this issue, yet most focused on separate aspects such as content delivery, algorithm implementation, or gamification, without integrating them into a cohesive learning platform. This study aims to develop Decodify, a web-based cryptography education platform that integrates structured learning materials, multi-algorithm encryption and decryption simulation, step-by-step data transformation visualization, and brute force attack simulation within a unified environment. The platform was developed using the Rapid Application Development (RAD) method, consisting of four phases: Requirement Planning, User Design, Construction, and Cutover. The result is an interactive web-based platform that enables users to learn cryptography concepts comprehensively, from theoretical foundations to practical algorithm implementation and security testing. Decodify bridges the gap between abstract theoretical concepts and hands-on practice, providing a more contextual and engaging learning experience.